Forage Research Strategy for The Development of Goat Production in Indonesia - Tatang M Ibrahim (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2003)
The development of goat for meat production has to be conducted and forage technology is needed to achieve the expected target of productivity. These forage technology have to be correctly designed for each existing major farming system within each regional developmental zone. It is therefore necessary to have national or regional agreement on zone where goat production should be developed. A general scheme for forage research basically involving 6 stages of evaluation, i.e., (1) germplasm collection; (2) multi-site testing of single accession; (3) swards productivity of selected accessions under cutting regime; (4) small plots for grazing evaluation, (5) large scale animal production assessment and (6) farm demonstration and commercial release. Many research results on forage technology currently available and generally had already passed the 2nd  stage of evaluation. However, the multiplication of planting material should be prioritized. It also necessary to have active involvement of provincial AIAT (Assessment Institute for Agricultural Technology) in advance stages of evaluation (5th and 6th stages). Relevant training and education for researchers, extensionists and farmers is needed to build up a strong support for high quality research results.  Key words: